SCIENTISTS AND RELIGIOUS COMMUNITIES: INVESTIGATING PERCEPTIONS, BUILDING UNDERSTANDING. - Wiseman, Jennifer; Arveson, Paul (Zygon: Journal of Religion & Science, 2014)
The American Association for the Advancement of Science (AAAS) Dialogue on Science, Ethics, and Religion (DoSER) program has embarked on an exciting project, 'Scientists and Religious Communities: Investigating Perceptions to Build Understanding.' The project will provide the first quantitative data on the underlying assumptions and concerns that shape national attitudes on science. A nationally representative survey conducted in collaboration with sociologists at Rice University has reached 10,000 people, including evangelical Christians, mainline Protestants, Catholics, and Jews. The survey probed how a broad range of religious people, particularly evangelical Christians, understands and thinks about science, and what they perceive about scientists. Scientists, broadly defined, were likewise surveyed to gauge their perceptions of how religious people regard science. The goal for AAAS is to increase understanding between the scientific and evangelical Christian communities and redefine this critical relationship. DoSER will bring together leaders from scientific and evangelical communities to discuss the implications of survey results and to use them for building better understanding and communication strategies. Building relationships between scientists and religious communities has the potential to create a new paradigm of understanding. Finding out what each group actually thinks, through a survey, is only the beginning.